The Use of E-learning In Literature Classes During Covid-19 : The Case Study of Master One Students at The Department of English-University of Laghouat - Rahmoune, Rania Noual; Hachani, Siham (Faculty of Letters and Foreign Languages Department of English, 2024)
The spread of COVID-19 creates an imminent danger to humanity because it has caused numerous international activities, especially educational ones, to be suspended. Despite the difficulties posed by this abrupt shift, educational institutions have been forced to switch to e-learning using accessible educational platforms to save the educational system. Therefore, the present study was conducted to evaluate the use of e-learning during the period of Covid19 in learning /teaching EFL literature to Master 01 students at the University of Amar Thelidji, the specific objectives include pinpointing the effectiveness and the challenges of using E-Learning to learn English literature during the Covid-19 pandemic, and evaluating both teachers’ and students' attitudes toward the incorporation of E-Learning in the learning process. In this study, two research instruments were used, a questionnaire with master 01 students followed by a semi structured interview addressed to five teachers. The study's findings support the claim that EFL teachers and students were enthusiastic about using elearning during the epidemic because they were concerned that the learning process might not survive the pandemic after all, much like many other areas of life. Nevertheless, it was saved by using online learning. Overall, this descriptive analytical study's findings are consistent with the hypothesis that e-learning is similar to flipping a coin. On the one hand, it is an effective way to study literature content. On the other one, it has some shortcomings that must be enhanced to better loosen the learning process.